Rural Education Studies Laboratory - LECAMPO and its repercussions on teaching, research and extension in Baixo Jaguaribe, Ceará (Research, Society and Development, 2022)
In this article, we aim to analyze the impact of the insertion of the Laboratory of Rural Education Studies - LECAMPO in the Vale do Jaguaribe region, precisely in Baixo Jaguaribe, Ceará. Of a qualitative nature, this work combines documental and bibliographic research, from different sources, namely: the Internal Regulations and the Report of Graduates and Collaborators of the Laboratory; the Institutional Repositories of the State University of Ceará and the Federal University of Ceará, as well as the SciELO - Brazil Platform, in which some of the diverse research developed by the members of LECAMPO are published. In our findings, we were able to understand that, over its 14 years of operation, LECAMPO formed professionals who currently form part of the municipal, state and federal education networks, working at different levels and modalities of education. Nevertheless, the Laboratory has been promoting critical (initial and continuing) teacher training, through teaching, research and extension, focusing on diverse and contextualized themes and consolidating itself as an academic space for the construction and socialization of knowledge engaged with peasant resistance, as well as articulated with the challenges of formal and non-formal education in the region.